Mechanisms of vasodilatation in pregnancy: studies of the role of prostaglandins and nitric-oxide in changes of vascular reactivity in the in situ blood perfused mesentery of pregnant rats. - Chu, Z. M. (Nature Publishing Group, 1993)
1. To examine the possible mechanisms of the vasodilatation and blunted pressor responses in late pregnancy, we have studied vascular reactivity of the in situ blood perfused mesenteric resistance vessels of 18-20 day pregnant Wistar-Kyoto rats (WKY). 2. Intra-arterial mean blood pressure (MBP) was lower in pregnant rats than in nonpregnant controls. There was no significant difference in basal mesenteric perfusion pressure (BPP) between groups. 3. Vascular reactivity to electrical stimulation (ES) or intra-arterial noradrenaline (NA), angiotensin II (AII) and arginine vasopressin (AVP) was decreased in the preparations from pregnant rats compared to that from nonpregnant controls. Noradrenaline spillover into mesenteric venous blood following ES was similar in pregnant and nonpregnant animals. 4. Indomethacin (5 mg kg-1, i.v.), an inhibitor of cyclo-oxygenase, induced significant increases in reactivity to ES in both pregnant and nonpregnant groups while potentiating the responses to NA and AII in nonpregnant animals only and having no effect on AVP-induced contractions in the preparations from either pregnant or nonpregnant animals. 5. NG-nitro-L-arginine (L-NOARG) (5 mg kg-1, i.v.), an inhibitor of nitric-oxide synthase, increased MBP and BPP in both pregnant and nonpregnant animals, but the difference in MBP between groups was still evident. 6. L-NOARG enhanced mesenteric vascular responses to ES, NA and AII in both pregnant and nonpregnant groups. Only the difference in NA responses between groups was abolished after pretreatment with L-NOARG. 7. These data show that vasoconstrictor responses to a variety of agonists are decreased in the in situ blood-perfused mesenteric resistance vessels of pregnant rats.(ABSTRACT TRUNCATED AT 250 WORDS)